Generic competitive strategies on organizational performance in Nepalese Commercial Banks - Upadhyay, Jitendra Pd.; Adhikari, Pitri Raj (Pravaha, 2020)
This paper attempts to examine the impact of generic competitive strategy on organizational performance in Nepalese commercial banks. It has employed descriptive and causal comparative research design to estimate the relationship between dependent variable (organizational performance) with independent variables (differentiation strategy, cost leadership strategy, focus strategy, organization’s core competency and bank size). Data has been collected from 384respondents by using structured questionnaire. The multiple regression model has been used to test the relationship. It is found that organizational performance of banks is influenced by cost leadership, differentiation, focus, organization ‘score competency and bank size.